Ergonomic analysis of gaming mouse using electromyography and subjective assessment - Zafs, Rizqie Anandita; Riyadi, Slamet; Sanjaya, Kadek Heri; Sya’Bana, Yukhi Mustaqim Kusuma; Dewi, Nugrahaning Sani; Tajalli, Muqorob; Yusuf, Sharfiden Hassen (National Research and Innovation Agency, 2024)
First Person Shooter (FPS) gamers usually use mice intensively, which may lead to musculoskeletal disorders. The objective of this study is to investigate the effect of the three most popular gaming mice designs on arm muscle activity and subjective perception to find the most optimum design. Subjects who participated in this study were ten healthy young adult males (age 18-24 years) selected from FPS gamers. The mice were tested when the subjects played the FPS Valorant game. The activity of forearm muscles, namely flexor carpi radialis (FCR) and palmaris longus (PL), was measured using electromyography (EMG). One-way analysis of variance (ANOVA) was used to compare the muscular activities when using the three mice. This study also measured the subjective perception of the participants. The study reveals that the high activation of muscles confirms the risk of Carpal Tunnel Syndrome (CTS). However, the difference in muscular activities between the three mice was found to be insignificant. On the other hand, the qualitative analysis suggests that the third mouse showed the evenest distribution of muscular activity both at low cycle and high cycle performance. Further study using psychophysiological methods is necessary to measure subjective preferences.